The Loneliness of infertile woman A survey field study in governorate of Lattakia - shrif, Leila; kheileh, reem; Khaska, Samar (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to know the Psychological Loneliness in a sample of infertility women in Lattakia in Syrian Arab Republic and to known differences between sample search on the variables of the study: Residence (rural, city), work (working, non-working), the education level (illiteracy erasure , preparatory , secondary , academic , higher of academic) . the study has been adopted the descriptive , method the researcher has taken the scale method as a main tool to take the opinions of the members the questionnaire has been accomplished by the Loneliness scale and it was applied on a sample consisting of 47 women were selected randomly. Results: found by Moderately among a sample search of infertile women. The Loneliness- - There are no differences have statistical indication on at the level of significance (0.05)among a sample search of infertile women in Lattakiah members of the on a scale the Psychological Loneliness according to marriage years number variable.( Less than ten years,Ten years and over). - There are no differences have statistical indication on at the level of significance (0.05)among a sample search of infertile women in the province of Lattakiah members on a scale the Psychological Loneliness according to work variable (does not work, work). - There are differences have statistical indication on at the level of significance (0.05) among a sample search of infertile women in the province of Lattakiah on a scale the Psychological Loneliness according to variable place of residence(city , rural) - There are no differences have statistical indication on at the level of significance (0.05) among a sample search of infertile women in the province of Lattakiah on a scale the Psychological Loneliness according to the education level variable (illiteracy erasure , preparatory , secondary , academic , higher of academic).